What did they cover? : a cluster analysis of news stories published in the Botswana Daily News, January – December 2004 - Mogotsi, Isaac Carter (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2005.